Effectiveness of Collage-Based Art Therapy in Reducing Anxiety Among Children with Thalassemia - Soewito, Bambang; Susmini, Susmini; Warastuti, Widya; Yusuf, Baharuddin (Indonesian Journal of Global Health Research, 2024)
Art therapy has been increasingly recognized as an effective therapeutic intervention for managing various psychological issues, including anxiety, depression, and stress, especially in pediatric and geriatric populations. Collage-making, a form of art therapy, has shown promise in helping individuals express emotions, reduce anxiety, and improve mental well-being. Objective to explore the effects of art therapy using collage media on reducing anxiety in children with Thalassemia. A case study approach was employed with two subjects, one child and one elderly individual, who underwent three sessions of collage art therapy over the course of three days. Each session lasted 30 minutes and focused on creating collages that allowed participants to express their emotions and experiences. Anxiety levels were assessed using the Revised Children’s Manifest Anxiety Scale (RCMAS) for the child and a similar anxiety assessment tool for the elderly participant. The child showed a significant reduction in anxiety, with the RCMAS score decreasing from 24 (indicating moderate anxiety) to 8 (indicating no anxiety) after three sessions. The elderly participant also exhibited a decrease in anxiety levels, with the final anxiety score dropping from 25 to 10. Both participants reported feeling more relaxed and emotionally relieved after the sessions. Art therapy using collage media effectively reduced anxiety levels in both children and elderly individuals. The creative process of collage-making provided a safe and engaging outlet for emotional expression, helping to alleviate anxiety.